An augmented PID control structure to compensate for valve stiction. Issue 4 (2018) - di Capaci, Riccardo Bacci; Scali, Claudio
Abstract: It is well-known that valve stiction causes sustained oscillations on process variables when a traditional PID controller is implemented in the feed-back loop. In the literature, there is a vast collection of solid techniques to compensate for valve stiction which employ different approaches and require various prior knowledges on process and stiction dynamics. Among others methods, PID retuning or changes to the traditional algorithm and structure of PID can be useful solutions to mitigate or remove negative effects of valve stiction. Appropriate controller retuning can reduce significantly amplitude and frequency of oscillation, but it cannot remove the problem permanently. Modifying traditional PID algorithm or augmenting standard structure of the controller are also robust approaches for the scope. This paper briefly revises some PID-based stiction compensation techniques and illustrates a new version of stiction-aware PID. A standard PI(D) controller is augmented with a two-move compensator and, by monitoring the control error, it is able to remove effect of valve stiction and to guarantee set-point tracking and disturbance rejection. This PID-based structure requires the estimation of controller output associated with the desired valve position at steady-state and the estimate of valve stiction parameters.